2021
DOI: 10.1177/20417314211067004
|View full text |Cite
|
Sign up to set email alerts
|

Lightwave-reinforced stem cells with enhanced wound healing efficacy

Abstract: Comprehensive research has led to significant preclinical outcomes in modified human adipose-derived mesenchymal stem cells (hADSCs). Photobiomodulation (PBM), a technique to enhance the cellular capacity of stem cells, has attracted considerable attention owing to its effectiveness and safety. Here, we suggest a red organic light-emitting diode (OLED)-based PBM strategy to augment the therapeutic efficacy of hADSCs. In vitro assessments revealed that hADSCs basked in red OLED light exhibited enhanced angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…As a result, 14 articles were assessed for eligibility, resulting in nine articles that were included in this review. Five studies were disqualified because they did not fit our inclusion criteria, that is, three showed absent and/or unreliable light protocols (14–16), one did not report surface markers or differentiation assays for SCs (17) and one did not present nonirradiated SC group as a control group (18) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, 14 articles were assessed for eligibility, resulting in nine articles that were included in this review. Five studies were disqualified because they did not fit our inclusion criteria, that is, three showed absent and/or unreliable light protocols (14–16), one did not report surface markers or differentiation assays for SCs (17) and one did not present nonirradiated SC group as a control group (18) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on the wound healing effect of LED have demonstrated that LED stimulates the proliferation and migration of various types of cells while promoting angiogenesis, the expression of growth factors, and the production of collagen, thereby assisting the process of wound healing. 11 21 22 23 24 Recent studies have also applied OLEDs and observed improved cellular function and wound healing in vivo. 11 15 We performed cell scratch wound healing assay in vitro and observed that the migration ability of HDFs was significantly increased after exposure to 6 J/cm 2 OLED and LED, similar to the previous report on the positive effect of OLED on the fibroblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
“… 11 21 22 23 24 Recent studies have also applied OLEDs and observed improved cellular function and wound healing in vivo. 11 15 We performed cell scratch wound healing assay in vitro and observed that the migration ability of HDFs was significantly increased after exposure to 6 J/cm 2 OLED and LED, similar to the previous report on the positive effect of OLED on the fibroblast proliferation. 25 Additionally, our group performed in vivo study with animal mouse model to investigate skin rejuvenation effect of OLEDs on UV-exposed skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administering stem cells with a biomaterial carrier may mitigate the limitations associated with the number and viability of stem cells but needs extensive research [ 19 , 20 ]. Administration of preconditioned stem cells with photo-biomodulation is another strategy to enhance the viability and activity of stem cells to enhance angiogenesis and wound healing [ 68 , 69 , 70 ]. With the background of the complications associated with autologous MSCs, Palma et al [ 71 ] reported that one specific subpopulation derived from the Wharton’s jelly of the umbilical cord (ucMSC), the differentiated mesenchymal cells (DMCs), has the potential of improving wound healing with increased angiogenesis without any rejection of the transplanted cells in immunocompetent mice.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%